Automatic generation of Swarm Robotic behaviors using multi-objective evolution - Chin, Kim On; Teo, Jason; Azali, Saudi (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.